Analysis of irrigation systems using comparative performance indicators: a case study of two large scale irrigation systems in the upper Awash Basin - Beshir, A.; Awulachew, Seleshi Bekele (2008)
This research was conducted to introduce the concept of evaluating the countries large scale irrigation systems and using the IWMI?s minimum set of indicators for the same purpose. This was done by selecting two irrigation systems in the Upper Awash Basin. NuraEra state and Wonji estate farm were selected for their relatively better organization and management, nearness to weather station and their representative nature of the large scale irrigation systems in the country. The necessary primary and secondary data to calculate the nine indicators were collected which are measurement of canal capacity and pump capacity, and total yields, farm gate prices of irrigated crops, area irrigated per crop per season or per year, crop types, production per season or per year, incomes generated from water fee and cropping pattern. The indicators used are output per cropped area, output per command area, output per irrigation diverted, output per water consumed, relative water supply, relative irrigation supply, water delivery capacity, financial self sufficiency and gross return on investment. The result of the analysis shows that the ratio of RWS, RIS and WDC for NuraEra are 4.8, 6.6 and 1.4, for Wonji estate 1.36, 1.4 and 0.77 respectively. The four agricultural indicators; output per cropped area, output per command, output per irrigation supply and output per water consumed are in the order of 21017.44, 23791.21, 0.74 and 2.3 for NuraEra and 20074.97, 13916.03, 1.4 and 1.2 for Wonji, respectively. NuraEra spent 0.36 percent of its income in the year of analysis and that of Wonji is 0.17 percent for operation and maintenance of the delivery system. FSS was 100% for both of the farms. And gross return on investment was 84.7% for NuraEra and 76.8% for Wonji.